2006
DOI: 10.1038/labinvest.3700418
|View full text |Cite
|
Sign up to set email alerts
|

Glucose enhances mesangial cell apoptosis

Abstract: Mesangial cell apoptosis occurs in experimental diabetic nephropathy, and this correlates with worsening albuminuria. This study examines the mechanism by which glucose modulates mesangial cell apoptosis. Apoptosis was induced in mesangial cells by serum deprivation in the presence of 5 or 25 mM D-glucose, and examined by expression of Annexin-V and disruption of mitochondrial transmembrane potential. Involvement of Bax, Bcl-2 and NF-jB were examined by RT-PCR and EMSA. Involvement of TGF-b1 was sought by dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 54 publications
(57 reference statements)
6
40
0
2
Order By: Relevance
“…Mesangial cell response to pathological stimuli is associated with the main events of glomerular injury and is important for resistance to glycoxidative stress through an antioxidant response (6). A previous study reported that alterations in glucose associated with diabetes mellitus induce mesangial cell apoptosis and contribute to diabetic nephropathy (7). However, the mechanism by which mesangial cell apoptosis is regulated in diabetic individuals remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Mesangial cell response to pathological stimuli is associated with the main events of glomerular injury and is important for resistance to glycoxidative stress through an antioxidant response (6). A previous study reported that alterations in glucose associated with diabetes mellitus induce mesangial cell apoptosis and contribute to diabetic nephropathy (7). However, the mechanism by which mesangial cell apoptosis is regulated in diabetic individuals remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In an environment of high glucose (HG), renal mesangial cells undergo cascades of deleterious reactions, including cell injury and extracellular matrix deposition, which lead to glomeruli dysfunction (1,25,49). Mesangial cell apoptosis promoted by HG contributes to the development of diabetic nephropathy (22,40).…”
Section: Shmentioning
confidence: 99%
“…11,12 Mesangial cell apoptosis can further promote the development of DN. [13][14][15] As DN progresses, ECM, which includes collagen IV, is deposited in the mesangium, causing gradual obliteration of glomerular capillary loops and progressive decline in glomerular filtration. 16 Mitochondria are the essential organelle in cell life and death, whose damage endangers lipid protein synthesis, cell oxidative phosphorylation, ATP production in cell metabolism and regulation of cellular steady state.…”
Section: Introductionmentioning
confidence: 99%